Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To find the length of the longer leg [tex]\( l \)[/tex] in terms of the hypotenuse [tex]\( h \)[/tex], let's start by understanding the given information.
1. Let the shorter leg be denoted by [tex]\( a \)[/tex].
2. The hypotenuse, [tex]\( h \)[/tex], is three times the shorter leg, [tex]\( a \)[/tex]. Therefore, [tex]\( h = 3a \)[/tex].
3. Let the longer leg be denoted by [tex]\( l \)[/tex].
Using the Pythagorean Theorem for a right triangle:
[tex]\[ h^2 = a^2 + l^2 \][/tex]
Since the hypotenuse [tex]\( h \)[/tex] is [tex]\( 3a \)[/tex], substitute [tex]\( h = 3a \)[/tex] into the Pythagorean Theorem:
[tex]\[ (3a)^2 = a^2 + l^2 \][/tex]
[tex]\[ 9a^2 = a^2 + l^2 \][/tex]
Rearrange this equation to isolate [tex]\( l^2 \)[/tex]:
[tex]\[ 9a^2 - a^2 = l^2 \][/tex]
[tex]\[ 8a^2 = l^2 \][/tex]
To find [tex]\( l \)[/tex], take the square root of both sides:
[tex]\[ l = \sqrt{8a^2} \][/tex]
[tex]\[ l = \sqrt{8} \cdot a \][/tex]
[tex]\[ l = 2\sqrt{2} \cdot a \][/tex]
Now express [tex]\( a \)[/tex] in terms of [tex]\( h \)[/tex]. Since [tex]\( h = 3a \)[/tex]:
[tex]\[ a = \frac{h}{3} \][/tex]
Substitute [tex]\( a \)[/tex] back into the expression for [tex]\( l \)[/tex]:
[tex]\[ l = 2\sqrt{2} \cdot \frac{h}{3} \][/tex]
[tex]\[ l = \frac{2\sqrt{2}}{3} \cdot h \][/tex]
Thus, the length of the longer leg [tex]\( l \)[/tex] in terms of the hypotenuse [tex]\( h \)[/tex] is:
[tex]\[ l = \frac{2\sqrt{2}}{3} \cdot h \][/tex]
In simplest form, the equation is:
[tex]\[ l = 2\sqrt{2} \cdot \frac{h}{3} \][/tex]
So, the answer in the required format is:
[tex]\[ I = 2 \sqrt{2} h / 3 \][/tex]
1. Let the shorter leg be denoted by [tex]\( a \)[/tex].
2. The hypotenuse, [tex]\( h \)[/tex], is three times the shorter leg, [tex]\( a \)[/tex]. Therefore, [tex]\( h = 3a \)[/tex].
3. Let the longer leg be denoted by [tex]\( l \)[/tex].
Using the Pythagorean Theorem for a right triangle:
[tex]\[ h^2 = a^2 + l^2 \][/tex]
Since the hypotenuse [tex]\( h \)[/tex] is [tex]\( 3a \)[/tex], substitute [tex]\( h = 3a \)[/tex] into the Pythagorean Theorem:
[tex]\[ (3a)^2 = a^2 + l^2 \][/tex]
[tex]\[ 9a^2 = a^2 + l^2 \][/tex]
Rearrange this equation to isolate [tex]\( l^2 \)[/tex]:
[tex]\[ 9a^2 - a^2 = l^2 \][/tex]
[tex]\[ 8a^2 = l^2 \][/tex]
To find [tex]\( l \)[/tex], take the square root of both sides:
[tex]\[ l = \sqrt{8a^2} \][/tex]
[tex]\[ l = \sqrt{8} \cdot a \][/tex]
[tex]\[ l = 2\sqrt{2} \cdot a \][/tex]
Now express [tex]\( a \)[/tex] in terms of [tex]\( h \)[/tex]. Since [tex]\( h = 3a \)[/tex]:
[tex]\[ a = \frac{h}{3} \][/tex]
Substitute [tex]\( a \)[/tex] back into the expression for [tex]\( l \)[/tex]:
[tex]\[ l = 2\sqrt{2} \cdot \frac{h}{3} \][/tex]
[tex]\[ l = \frac{2\sqrt{2}}{3} \cdot h \][/tex]
Thus, the length of the longer leg [tex]\( l \)[/tex] in terms of the hypotenuse [tex]\( h \)[/tex] is:
[tex]\[ l = \frac{2\sqrt{2}}{3} \cdot h \][/tex]
In simplest form, the equation is:
[tex]\[ l = 2\sqrt{2} \cdot \frac{h}{3} \][/tex]
So, the answer in the required format is:
[tex]\[ I = 2 \sqrt{2} h / 3 \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.